2018
DOI: 10.1007/s11469-018-9892-x
|View full text |Cite
|
Sign up to set email alerts
|

Global Limit Setting as a Responsible Gambling Tool: What Do Players Think?

Abstract: Many companies offer tools to help their clientele gamble more responsibly. Such tools include pre-commitment facilities where the gambler can set voluntary time and money limits. However, empirical evidence is lacking as to whether voluntary or mandatory limit setting has any positive impact on subsequent gambling behavior and whether such measures are of help to high-intensity and/or problem gamblers. In the present study, 2352 gamblers who had played games with Norsk Tipping (NT), the Norwegian Government-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 18 publications
5
37
1
1
Order By: Relevance
“…This means that limits are generally set in a realistic range of the actual gambling behaviour. This supports previous findings which report that the majority of players think that voluntary spending limits are a useful RG feature (International Gaming Research Unit 2007;Griffiths et al 2009;Auer et al 2018a). Voluntary money limits are not useful if the limits chosen are much higher than the actual gambling habits because they will not help the player to control excessive gambling.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This means that limits are generally set in a realistic range of the actual gambling behaviour. This supports previous findings which report that the majority of players think that voluntary spending limits are a useful RG feature (International Gaming Research Unit 2007;Griffiths et al 2009;Auer et al 2018a). Voluntary money limits are not useful if the limits chosen are much higher than the actual gambling habits because they will not help the player to control excessive gambling.…”
Section: Discussionsupporting
confidence: 88%
“…The extent to which voluntary limits are used strongly depends on a gaming operator's overall RG strategy. Some companies require all players to choose a limit, and/or have maximum loss limits whereas other operators offer limit-setting as an entirely voluntary tool (Auer et al 2018a). The authors believe that the present study's result is an important argument for player protection because it demonstrates that voluntary limitsetting does not increase players' inactivity.…”
Section: Discussionmentioning
confidence: 57%
“…The reported reasons for tool use indicate that many participants were seeking to be proactive in ensuring that they were gambling at sustainable levels, and a notable proportion of those using limits and time-outs did so to avoid developing gambling problems. This supports findings from a Swedish Internet gambling study indicating that 23% of users of consumer protection tools used these to play safely (Griffiths et al, 2009) and a Norwegian study which found more positive attitudes towards limit setting among low-risk compared to high-risk gamblers (Auer, Reiestad, & Griffiths, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…The second and third most common sources of frustration were the voluntary nature of the limits in the RG tool in question (as opposed to mandatory) and the fact that RG tools let the user's winnings compensate for the wagered money distorting the picture of how much money was invested in gambling, both points indicating a demand for stricter RG tools ( Griffiths et al, 2009 ). A recent survey of Norwegian gamblers found a more positive attitude towards a global limit setting among low-risk compared to high-risk gamblers ( Auer, Reiestad, & Griffiths, 2018 ). A Swedish longitudinal study found that unregulated Internet operators had the highest proportion of problem gamblers among their customers compared to the regulated market ( Svensson & Romild, 2011 ), suggesting that recreational gamblers are not the category at highest risk of abandoning the legal gambling market, that is often obliged to implement RG tools.…”
Section: Introductionmentioning
confidence: 99%